A possible new mechanism and drug intervention for kidney damage due to arsenic poisoning in rats. Issue 2 (14th January 2016) - Xu, Yu-yan; Zeng, Qi-bing; Yao, Mao-lin; Yu, Chun; Li, Jun; Zhang, Ai-hua
Graphical Abstract: Abstract: Arsenic poisoning is a worldwide endemic disease that affects thousands of people. Currently, the aetiology of the disease is known, but its pathogenesis is uncharacterized and there is no specific treatment. We established a rat model of coal-burning arsenic poisoning by feeding the animals corn powder baked with high arsenic coal. By observing subsequent changes in kidney and immune function, we found that arsenic induces both kidney and immune damage. Furthermore, there is a significant correlation between kidney and immune damage. Moreover, Ginkgo biloba, a known immune enhancer, was used as an intervention agent in arsenic poisoned rats to validate the relationship between kidney and immune damage. Meanwhile, we also explored the mechanism of Ginkgo biloba treatment of kidney damage in burning-coal arsenic poisoned rats. We found that Ginkgo biloba enhanced immune function in rats with arsenic poisoning and ameliorated arsenic-induced kidney damage. These results suggest that immune suppression may be one of the mechanisms underlying arsenic-induced kidney damage and that Ginkgo biloba might relieve kidney damage by enhancing immune function.